1999
DOI: 10.1177/0256090919990406
|View full text |Cite
|
Sign up to set email alerts
|

Dividend and Bonus Policies of Indian Companies: An Analysis

Abstract: This article presents the findings of a study of dividend paying behaviour of more than 200 Indian companies over 15 years. It attempts to examine whether the companies offering bonus issue have been able to generate greater returns for their shareholders than those that have not offered any bonus issue but have maintained a steadily increasing dividend rate. It is found that most of the companies either maintained the dividend rate after the bonus issue at the pre-bonus level or decreased it (but not proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The major determinants of dividend payout policy of firms are the systematic risk, firms' number of common stockholders, forecasted growth rate of earnings and past revenue growth rate (Sexena, 1999). Mohanty (1999) examines the dividend policy of 200 companies for the period of 15 years to find the impact of bonus issue on the behavior of dividend paying companies and find that the dividend rates are the main factor deciding the dividend policy as compared to dividend payout ratio. Mahakud (2005) examines the impact of shareholding pattern on dividend pay-out ratio of the Indian companies listed in Bombay Stock Exchange (BSE) during 2001-2004 and finds that the lagged earnings, sales and size of the company are positively associated, whereas, debt-to-equity ratio and institutional shareholding pattern are negatively associated with the dividend payment decision.…”
Section: Business and Economic Researchmentioning
confidence: 99%
“…The major determinants of dividend payout policy of firms are the systematic risk, firms' number of common stockholders, forecasted growth rate of earnings and past revenue growth rate (Sexena, 1999). Mohanty (1999) examines the dividend policy of 200 companies for the period of 15 years to find the impact of bonus issue on the behavior of dividend paying companies and find that the dividend rates are the main factor deciding the dividend policy as compared to dividend payout ratio. Mahakud (2005) examines the impact of shareholding pattern on dividend pay-out ratio of the Indian companies listed in Bombay Stock Exchange (BSE) during 2001-2004 and finds that the lagged earnings, sales and size of the company are positively associated, whereas, debt-to-equity ratio and institutional shareholding pattern are negatively associated with the dividend payment decision.…”
Section: Business and Economic Researchmentioning
confidence: 99%
“…Bhat and Pandey (1994) are of the view that firms do not necessarily have targeted dividend ratio as their survey finds that management of the firms believes dividend changes are due to increased level of earnings by firm. Also Mohanty (1999)'s paper shows that Indian companies' payout reflects that companies do maintain constant payout but have fluctuating payout ratio as a result of level of profits.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…In a nutshell, there are several hypotheses put forward to explain the positive abnormal returns associated with bonus announcements. Mohanty (1999) found that firms which issued bonus shares, have either maintained the payout at the pre-bonus level or only decreased it marginally thereby increasing the payout to shareholders. Papaioannou et al (2000) found no significant abnormal returns on and around announcement period as in Greece it is compulsory requirements imposed upon firms to satisfy the legal requirements a However their research environment is quite different from other markets, stock dividends in Greece are not initiated by firms but they are compulsory requirements imposed upon firms to satisfy legal requirements and any stock dividend announcement should get the approval ISSN 1946-052X 2013 www.macrothink.org/ajfa from the shareholders along with the terms of the distribution.…”
Section: Review Of Literaturementioning
confidence: 97%